Environmental Risks and Agricultural Commodities - Dezfouli, Kaveh Moradi; Walker, Thomas J. (Journal of Applied Business and Economics, 2024)
As natural disasters are expected to increase both in severity and frequency, their impact on agricultural commodities and the food supply chain is likely to rise in tandem. We use a unique data set of natural disasters that occurred globally between 1970 and 2015 and study their impact on the price and price volatility of eight globally traded agricultural commodities that account for more than 75% of the food supply in the world. Our results show that price and the price volatility of commodities are impacted around the occurrence of a natural disaster in producing countries. In addition, we find that the affected country’s production shares, the total damage caused by a natural disaster relative to the affected country’s GDP, and the demand pressure for the commodity have an impact on the magnitude of price and price volatility changes of a given commodity around the occurrence of a natural disaster.